Caracterização físico-química de óleos e gorduras residuais e avaliação de métodos de transesterificação para obtenção de biodiesel - Canesin, Edmilson Antonio (2013)
This work presented as main objective to develop a procedure of acid catalysis, using ethanol compared to the other two procedures basic catalysis, one methyl and one ethyl, to conduct transesterification reactions in residual bovine and chickens oils collected in commercial gas furnaces to produce biodiesel. Preliminary analysis of physicochemical properties such as acidity (IA), saponification number (IS), percentage of ester, peroxide value (IP), iodine value (InI), infrared spectroscopy (IV) and humidity Karl Fischer (KF) were performed on samples of waste oil to initially check whether they had minimum conditions, according to the National Agency of Petroleum, Natural Gas and Biofuels (ANP), for use in biodiesel production. Verifying the viability production, the samples were quantified by four transesterification methods, using acidic and basic catalysis described in the literature, Bannon et al., (1982) (BA), ISO 5509, (1978) (ISO), Hartman and Lago (1973) (HL) and Jham et al., (1982) (JA) by gas chromatography with flame ionization detection (GC-FID). These measurements allowed us to verify that the residual oils from bovine and chickens, showed a predominant chemical composition of saturated fatty acids (SFA) and monounsaturated fatty acids (MUFA), unlike traditional soybean oil which showed a predominant content of polyunsaturated fatty acids (PUFA). After this step syntheses were carried out using three biodiesel catalytic different routes: methylic synthesis (KOH 1.25% w/v; molar ratio 6:1 at 60C for 20 min); ethylic synthesis (1.0% KOH w/v; molar ratio 9:1 at 40C for 20 min) and ethylic synthesis (H2SO4 and AlCl3 1.75% to 0.5% w/v; molar ratio of 12:1 at 80C for 180 min) followed by a basic stage (2.0% NaOH, molar ratio 3:1 at 40C for 5 min), three samples of bovine residual oils, two samples of chickens, one sample of residual soybean oil, one sample of new soybean oil and a blend formed by 15% residual soybean oil and 85% bovine tallow residual (by mass). The biodiesel samples obtained were characterized according to some physicochemical parameters: kinematic viscosity (), flash point, fire point, density, humidity KF, InI, IA, free glycerin (GL) total glycerin (GT) and temperature distillation (90%), and in general all met the specifications set by the American Society for Testing and Materials (ASTM), European Normalization (EN) and ANP, and as expected, the variable composition of FAME influenced the properties of biodiesel produced, as the higher viscosity of the samples ethylic, a significant reduction in unsaturated ethyl biodiesel that was subjected to acid catalysis, a rise in temperature of the flash point and distillation (90%) of the samples which predominated SFA and MUFA. The acid catalysis proposal was effective for samples of residual oils from cattle and chickens, yield up to 85.21% by weight but not exceeded the yield of ethyl basic catalysis, which has reached 91.83% by mass for residual chickens oils. It was concluded that, even presenting degraded with peroxide values (IP) and acidity (IA) high (89.35 meq O2 kg-1 and 3.41 mg KOH g-1 respectively) waste oils are still good potential biodiesel producers, the identification and quantification of fatty acids influences the reaction proceeds and the proposed catalytic process is effective for use in residual matrices, producing biodiesel that meets the standards of the ANP